The Development of English E-Worksheet using Wizer.me - Viona Venssia Devaldi; Diana Oktavia; Winda Trisnawati (UM Purwokerto Press, 2024)
This research was conducted to develop more various teaching materials in English subject. Based on the observation and interview conducted by researcher in SMAN 1 Bungo, it was found that the students do not like monotonous learning in English class. Therefore, the English teacher used the electronic teaching materials and media to support the teaching and learning process. Moreover, the students are allowed to use cellphone and laptop to support their studying. To provide more various teaching materials, the research used research and development or R&D methods within ADDIE model. The research subjects were grade 10 students at Senior High School. The instrument used in this research is the process of designing E-Worksheet using Wizer.me, after that Experts of Validation which consists of content experts and media experts. The last is the Practicality questionnaire. The validity results have been tested by four experts which include content experts and media experts. The validity test conducted by content experts obtained a percentage of 73% and 91% which means fairly valid and very valid, then media experts obtained a percentage of 85% and 93% which means very valid. Moreover, the results of the effectiveness of E-Worksheet that were tested on students and teachers obtained a percentage of 91% and 93% which were categorized as very effective.